(untitled) (Socio-Economic Development Panorama, 2009)
Micro Finance (MF) has been used as poverty lessening device by developing countries of the world. Nepal has been using this tool for more than three decades for poverty lessening programs by government, Nepal Rastra Bank (NRB) and other MF Institutions (MFIs) for more than three decades. Despite this, the outreach of MF has been clustered in accessible region and areas of the country. Majority of needy poorest of the poor and destitute are found to be still bypassed or untouched by various MF programs in Nepal. Without awarding proper access of finance to the poorest of the poor, neither Millennium Development Goals (MDGs) nor programs related to MF as launched by government, NRB, MFIs, etc would become successful. Outreach situation is still not yet satisfactory. For this all players and actors in MF sector should move hand in hand in policy, program, and activities interwoven with MF. Additionally, the success of 11th Three year Interim Plan lies on the move to amicably structure the outreach of MF especially in rural and remote areas of Nepal, where there is paucity of petty capital to conduct heterogeneous income generating activities through meaningful blending with local resources. Key Words: Micro Finance; MF; NRB; rural population; self help group; micro-credit; poverty Socio Economic Development Panorama; Vol. 1; No. 4, 2009; January-June